2009
DOI: 10.1088/0004-637x/703/2/2082
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Magnification Microlensing Event Ogle-2008-BLG-279: Strong Limits on Planetary Companions to the Lens Star

Abstract: parallax, from which we determine the mass of the lens, M l = 0.64 ± 0.10 M , and its distance, D l = 4.0 ± 0.6 kpc. We rule out Jupiter-mass planetary companions to the lens star for projected separations in the range 0.5-20 AU. More generally, we find that this event was sensitive to planets with masses as small as 0.2 M ⊕ 2 M Mars with projected separations near the Einstein ring (∼3 AU).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…The determined angular radius of the source star is θ = 6.11 ± 0.53 μas, implying that the source star is a Galactic bulge clump giant star. The uncertainty of θ is estimated from the combination of those of the colors and magnitudes of the source and the clump centroid and an additional 7% intrinsic error in the conversion process from the color to the source radius (Yee et al 2009). Then, the Einstein radius is measured as…”
Section: Resultsmentioning
confidence: 99%
“…The determined angular radius of the source star is θ = 6.11 ± 0.53 μas, implying that the source star is a Galactic bulge clump giant star. The uncertainty of θ is estimated from the combination of those of the colors and magnitudes of the source and the clump centroid and an additional 7% intrinsic error in the conversion process from the color to the source radius (Yee et al 2009). Then, the Einstein radius is measured as…”
Section: Resultsmentioning
confidence: 99%
“…For observations towards the Galactic bulge, the sensitivity of gravitational microlensing to planets with masses much below that of Earth has already been demonstrated [74,103,157], and it has been pointed out that, already without deploying a space mission, one could reach down to objects similar to the moon [158,159].…”
Section: Future Directionsmentioning
confidence: 99%
“…From the observational side, the surveys Microlensing Planet Search (MPS) (Rhie 1999) and Microlensing Observations in Astrophysics (MOA) (Rhie et al 2000;Sumi et al 2003) demonstrated for the first time that microlensing technique is sensitive enough to detect earth-mass exoplanets. Shvartzvald et al (2017) show the possibility to detect Earth-mass Planet in a 1 AU Orbit around an Ultracool Dwarf and Yee et al (2009) present an extreme magnification microlensing event and its sensitivity to planets with masses as small as 0.2M ⊕ 2M M ars with projected separations near the Einstein ring ( 3 AU). Gould et al (2014) even showed the capability of microlensing technique to discover Earth-mass planets around 1 AU in binary systems.…”
Section: Introductionmentioning
confidence: 99%